The Effect of The Increase in POPFMA (Palm Oil Plantation Fund Management Agency) Grant Funds on Farmer Interest in The POR (People Oil Rejuvenation) Program with Strategic Partnership Pattern - Sulaiman, Novi; Arsjah, Regina Jansen (Manunggal Halim Jaya, 2025)
The People's Palm Oil Replanting Program (Peremajaan Sawit Rakyat or POR) is a strategic initiative by the Indonesian government aimed at improving the productivity of smallholder palm oil plantations through the replanting of unproductive trees. One form of government support for this program is through grant funding provided by the Indonesian Oil Palm Estate Fund (Palm Oil Plantation Fund Management Agency or POPFMA). As the allocation of these grants increases, questions arise regarding how the rise in funding influences farmers' interest in participating in the POR program, particularly through strategic partnership schemes involving core companies and farmer cooperatives. This study aims to analyze the effect of increased POPFMA grant funding on farmers' interest in joining the POR program through strategic partnership models. The research adopts a qualitative approach by comparing grant utilization and its impacts on cooperatives, farmers, surrounding communities, and the government. The findings indicate that the increase in POPFMA grant amounts positively affects farmers' willingness to participate in the POR program. This research is expected to provide empirical contributions to policy-making in empowering smallholder palm oil farmers, strengthening the effectiveness of the POR program, and supporting the sustainability of the national palm oil plantation sector. Furthermore, the results may serve as a basis for designing more inclusive and responsive partnership schemes that align with the needs of farmers.